2010
DOI: 10.1073/pnas.0914886107
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cost as a unifying principle governing neuronal biophysics

Abstract: The brain contains an astonishing diversity of neurons, each expressing only one set of ion channels out of the billions of potential channel combinations. Simple organizing principles are required for us to make sense of this abundance of possibilities and wealth of related data. We suggest that energy minimization subject to functional constraints may be one such unifying principle. We compared the energy needed to produce action potentials singly and in trains for a wide range of channel densities and kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
263
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(272 citation statements)
references
References 68 publications
9
263
0
Order By: Relevance
“…Another possibility is that improved neural efficiency, such as using less brain activity and/or optimizing motor unit recruitment, could reduce metabolic cost. Efficient neuronal signaling in the brain has been shown to correspond with energy minimization (Attwell and Laughlin, 2001;Hasenstaub et al, 2010). Information processing and neuronal signaling patterns also consume a large portion of the total energy used by the brain (Attwell and Laughlin, 2001;Magistretti, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that improved neural efficiency, such as using less brain activity and/or optimizing motor unit recruitment, could reduce metabolic cost. Efficient neuronal signaling in the brain has been shown to correspond with energy minimization (Attwell and Laughlin, 2001;Hasenstaub et al, 2010). Information processing and neuronal signaling patterns also consume a large portion of the total energy used by the brain (Attwell and Laughlin, 2001;Magistretti, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, energy-saving mechanisms that may partially compensate for the high ATP demand have been discussed for fast-spiking interneurons, i.e., fewer excitatory input sites, partially higher input resistance as well as expression of voltage-gated K þ -channels of the Kv3 subtype and rapidly inactivating Na þ -channels. 18,134,138,[140][141][142][143] Examples from the basal ganglia also suggest that high spiking rates of GABAergic neurons do not necessarily correlate with their energetic needs. 18 As long as we are lacking direct empirical evidence for the activity-dependent energy utilization of these interneurons, it will be difficult to decide how much energy is required to permit their fast-spiking behavior.…”
Section: Energy Utilization Of Fast-spiking Behavior and Synaptic Inhmentioning
confidence: 99%
“…When combined with details of molecular processes that occur within neurons, such as the structure of second messenger cascades, this approach can yield detailed energy budgets for neurons that quantify the consumption of specific processes. Moreover, when coupled with dynamic computational models [26,29,41], this approach can allow the energy consumption of neurons to be estimated on a fine temporal scale equivalent to that of the electrical signals within neurons themselves.…”
Section: Box 1 Measuring Energy Consumptionmentioning
confidence: 99%
“…It was assumed that the energy consumption of this action was broadly representative of other action potentials [9]; however, this was dispelled by combining experimental measurements and computational modelling of a range of action potentials primarily from mammalian neurons [26][27][28][29]. This demonstrated that the squid giant axon action potential was profligate in its energy consumption compared to most other action potentials, and revealed a hitherto unappreciated heterogeneity in the biophysics of the currents generating action potentials and their consequences for the energy consumption of the action potential [25][26][27][28][29][30][31][32][33][34][35][36]. The major cause of differences in energy consumption was identified as the overlap between the inward and outward currents during the action potential [26,28,34,35]: A large overlap inflates energy consumption whereas complete separation of the currents reduces energy consumption close to the minimum possible.…”
Section: Heterogeneity In Action Potential Costsmentioning
confidence: 99%
See 1 more Smart Citation